Self-esteem and academic stress in students of the Bachelor's Program in Desarrollo Humano of the Universidad Centroccidental Lisandro Alvarado (Mayéutica Revista Científica de Humanidades y Artes, 2016)
This research explored the relationship between academic stress and self -esteem in the Human Development Bachelor program of the UniversityCentroccidental Lisandro Alvarado(Barquisimeto-Venezuela). It’s assumed that both factors affect the behavior of individuals directly and,  therefore, according to the purposes of higher education, this Institution cannot ignore them in the process of comprehensive training of future professionals. This is a bibliographic, descriptive, non-experimental, field and cross-sectional documentary study. We used the Coopersmith Self-Esteem Inventory (Format C, for adults) and the university academic stress assessment questionnaire, which were applied to an intentional sample represented by students of the VIII and IX semesters, belonging to the 201 6- II. The results indicate that, in general, the scientific community is increasingly concerned about the study of both phenomena in the university field. In the selected institutional context, students have a high average of self-esteem of 47.9% and a high average of 37.5 %; in the stress case, students have a medium low level of 29.1 7%, and a25% low level; on the other hand, the completion of the Bachelor's degree in the stipulated term represents the most frequent stressor. The correlation between both variables, according to Pearson's index, was negative.
Keywords: sel esteem; academic stress; university students; human development